World Market Integration through the Lens of Foreign Direct Investors - Albuquerque, Rui; Loayza, Norman; Serven, Luis (World Bank, Washington, DC, 2014)
The authors analyze the unparalleled increase in foreign direct investment to emerging market economies in the past 25 years. Using a large cross-country time-series data set, the authors evaluate the dependence of foreign direct investment on global factors or worldwide sources of risk (that is, factors that drive foreign direct investment across several countries). They construct a globalization measure that equals the share of explained variation in direct investment attributable to global factors. The authors show that the globalization measure has increased steadily for industrial and developing countries. For the full sample of countries, the globalization measure rose eightfold from 1985 to 1999. Furthermore, in recent years developing countries' exposure to global factors has approached that of industrial countries, particularly for Latin America. Finally, the globalization measure correlates strongly with measures of capital market liberalization. Overall the authors find strong support for the hypothesis of increased market integration which implies a greater role for worldwide sources of risk. They discuss the implications of the results for public policies regarding capital market liberalization and policies directed at attracting foreign investment.